2013
DOI: 10.4141/cjps2012-273
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in white beans with postemergence herbicide tankmixes

Abstract: Soltani, N., Nurse, R. E. and Sikkema, P. H. 2013. Weed management in white beans with postemergence herbicide tankmixes. Can. J. Plant Sci. 93: 669–674. Weed control efficacy of cloransulam-methyl, halosulfuron, bentazon, fomesafen and their tankmixes applied post-emergence (POST) for weed management in white bean was evaluated in field studies conducted in four Ontario locations during 2008–2011. Cloransulam-methyl, halosulfuron, bentazon, fomesafen, bentazon plus fomesafen, cloransulam-methyl plus bentazon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 30 publications
6
28
1
1
Order By: Relevance
“…Similar results of redroot pigweed control with trifluralin, pendimethalin, EPTC, dimethenamid-P, and S-metolachlor were reported by Soltani et al (2012b). Halosulfuron applied POST controlled redroot pigweed 80% (Soltani et al 2013b). …”
Section: Redroot Pigweedsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results of redroot pigweed control with trifluralin, pendimethalin, EPTC, dimethenamid-P, and S-metolachlor were reported by Soltani et al (2012b). Halosulfuron applied POST controlled redroot pigweed 80% (Soltani et al 2013b). …”
Section: Redroot Pigweedsupporting
confidence: 72%
“…Soltani et al (2014a, b) reported that halosulfuron, halosulfuron + trifluralin, halosulfuron + S-metolachlor provided 90 to 98% common ragweed control. In another study, halosulfuron controlled common ragweed 91 to 94% (Soltani et al 2013b). Soltani et al (2012a, b) reported that trifluralin, pendimethalin, EPTC, dimethenamid-P and S-metolachlor provided 34, 20, 60, 26, and 50% common ragweed control at 8 WAE, respectively.…”
Section: Common Ragweedmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies supported that these herbicides cause low crop injury and little negative interference on the cropping yield on black, white and pinto beans (FONTES et al, 2001;HEKMAT et al, 2008;SOLTANI et al, 2013;LINHARES et al, 2014). However, imazamox at the rate of 129g a.i.…”
Section: Introductionmentioning
confidence: 99%
“…ha -1 is reported to cause crop injury of 8% at 14DAT on common beans, yet yield loss ranging from 29 to 43% (SOLTANI et al, 2013). The herbicide cloransulam has the potential to be used in common beans when tank mixed with bentazon, which promoted a safening (protects) effect on acetolactate synthase (ALS) herbicides by decreasing the rate of absorption and translocation throughout the plant; moreover, tank-mixing imazethapyr or cloransulam with bentazon, amplified the weed control spectrum (SOLTANI et al, 2012;SOLTANI et al, 2013). Diclosulam belongs to the group of the triazolopyrimidine, which is the same of the herbicide cloransulam (OLIVEIRA JR., 2011).…”
Section: Introductionmentioning
confidence: 99%